An analysis of species-groups of the genus Plinthisus Stephens (Hemiptera: Rhyparochromidae) in the Ethiopian Region with the description of eight new species - Sweet, Merrill H.; Slater, James A. (Zootaxa, 2004)
An analysis of the known Ethiopian Plinthisus fauna shows that there are at least 12 species-groups. Two groups, the subgenera Locutius and Isioscytus, have Old World Palearctic and tropicopolitan distributions that extend into Australia. The other 10 species-groups are endemic to Africa, nine having a center of endemicity in the Cape Region of South Africa with apparent relationships to the Australian fauna. Eight new species of Plinthisus are described, each as a representative of a distinct species-group, seven from South Africa: P. (Isioscytus) pulchellus n. sp, P. (Nanoplinthisus) ericae n. sp, P. (N.) fynbosi n. sp, P. (N.) peninsularis n. sp., P. (N.) lamprus n. sp., P. (N) zuurb- ergi n. sp., and P. (N.) drakensbergensis n. sp,; and one, P. (Plinthisus) brachyoccus n. sp., from the Democratic Republic of the Congo. P. beniamaricus Linnavuori, 1978 stat. nov. and P. kilimensis Horv th, 1906 stat. nov. are raised from subspecies of P. himyaritus Linnavuori, 1978 and P.afer Horv th, 1906, respectively to specific rank. Plinthisus hirsutus Slater, 1964 is placed in a species-group distinct from the subgenus Dasythisus. The Nearctic species Plinthisus americanus Van Duzee, 1910, P. compactus Uhler, 1904 and P. indentatus Barber, 1918 are placed in the subgenus Dasythisus. Included are 123 figures illustrating dorsal views, heads, metathoracic scent gland areas, metathoracic wing stridulitra, abdominal structure, male genital capsules, claspers, phalli, spermathecae, and prothoracic legs.